Expression of Potato StDRO1 in Arabidopsis Alters Root Architecture and Drought Tolerance - Sun, Chao; Liang, Wenjun; Yan, Kan; Xu, Derong; Qin, Tianyuan; Fiaz, Sajid; Kear, Philip; Bi, Zhenzhen; Liu, Yuhui; Liu, Zhen; Zhang, Junlian; Bai, Jiangping (Frontiers in Plant Science, 2022)
Potato (Solanum tuberosum L) is third important crop for providing calories to large human population, is considered sensitive to moderately sensitive to drought stress condition. The development of drought tolerant, elite varieties of potato is a challenging task which can be achieved through molecular breeding. Recently, Deeper Rooting 1 (DRO1) gene have been identified in rice influencing plant root system, regulating grain yield under drought stress condition. The potato StDRO1 protein is mainly localized at the plasma membrane of tobacco leaf cells, and over-expression analysis of StDRO1 in Arabidopsis resulted in an increased lateral root number yet decreases in lateral root angle, lateral branch angle, and the silique angle. Additionally, the drought treatment analysis indicated StDRO1 regulated the drought tolerance and rescued the defective root architecture and drought tolerant phenotypes of Atdro1, an Arabidopsis AtDRO1 null mutant. Furthermore, the StDRO1 expression was found significantly higher in drought tolerant potato cultivar “Unica” compared to drought-sensitive cultivar “Atlantic”. StDRO1 transcriptional response under drought stress occurred significantly earlier in Unica than in Atlantic. Collectively, the outcome of present investigation elucidated the role of DRO1 function in alternation of root architecture which potentially act as a key gene in development of drought stress tolerant cultivar. Furthermore, these findings will provide the theoretical basis for molecular breeding of drought tolerant potato cultivars for farming community.